Consolidated nuclear waste storage in Andrews, Texas: An integrated technical and policy risk analysis. Issue 1 (February 2023) - Mallette, Adam J.; Datta, Aparajita; Krishnamoorti, Ramanan
Over the last 50 years, nuclear energy has reduced US energy-related CO2 emissions by over 30 gigatons compared to if the same electricity were produced by fossil fuels such as coal and natural gas. However, many kilotons of spent nuclear fuel have accumulated at different sites across the country, and sociopolitical factors have frustrated efforts to address the challenge of nuclear waste disposal. Presently, a consolidated interim storage facility in Andrews, Texas, provides a promising temporary solution. In this paper, we compare the technical and policy risks of the project to continued storage at independent spent fuel storage installations. Our results indicate that the cost of the radiological risk is low (<30, 000) for both scenarios. However, policy and societal considerations will impact the viability of the proposed consolidated interim storage facility. The safety and suitability of this interim storage facility will be affected by when a permanent repository becomes available, whether insurance for offsite waste storage is available, and the impact of climate risks. Although a consolidated interim storage facility at Andrews can potentially serve as a safe and economically advantageous solution, we highlight why these concerns must be addressed for the successful implementation of this facility, and more broadly for the future of the US nuclear industry.